The Effectiveness of Honey Application for Oral Mucositis in Cancer Patients: A Review of Randomized Controlled Trials - Mathew Varghese V; Sneha Sara Sam (International Journal of Oncological Nursing and Practices, 2023)
Background: Oral mucositis (OM) is a prevalent and distressing adverse outcome of cancer therapies, including chemotherapy and radiation therapy. It is an inflammatory ailment that impacts the mucous membrane inside the mouth, tongue, gums, and throat. OM can cause pain, discomfort, difficulty swallowing, and in severe cases, it can lead to infection and delayed cancer treatment. Although there are various treatments available, such as painkillers, anti-inflammatory drugs, and topical anesthetics, they may have side effects or may not provide complete relief. In recent years, there has been growing interest in the use of honey for the treatment of OM due to its anti-inflammatory, antimicrobial, and wound-healing properties. Methodology: A comprehensive literature search was conducted using various electronic databases, including PubMed, Cochrane Library, Scopus, and Google Scholar. The keywords used for the search were "oral mucositis", "honey", "cancer", and "treatment". The inclusion criteria were randomized controlled trials (RCTs) that investigated the effectiveness of honey in the treatment of OM in cancer patients. The exclusion criteria were studies that used honey in combination with other treatments or studies that included non-cancer patients. Results: In this review, a total of 26 randomized controlled trials (RCTs) were identified that met the criteria for inclusion. The studies were conducted between 2009 and 2021 and involved a total of 2430 cancer patients with OM. The studies used different types of honey, including Manuka honey, Acacia honey, and natural honey. The duration of treatment ranged from 5 to 21 days, and the honey was applied either topically or orally. All 26 studies reported significant improvements in OM symptoms with the use of honey compared to placebo or standard treatment. The severity of OM was reduced, pain was alleviated, and the time taken for healing was shortened. Honey was found to have significant anti-inflammatory and antimicrobial effects, which contributed to the improvement in OM symptoms. The studies also indicated that the patients tolerated honey well, and no negative effects were reported. Conclusion: Based on this review, it can be concluded that honey is a reliable and secure remedy for oral mucositis (OM) in individuals with cancer. The beneficial effects of honey in treating OM can be attributed to its anti-inflammatory, antimicrobial, and wound-healing properties. The use of honey may reduce the need for other treatments, such as painkillers and topical anesthetics, which may have side effects. Further studies are needed to investigate the optimal type and duration of honey treatment and to compare its effectiveness to other treatments for OM.
Keywords: Honey; Oral mucositis; cancer patients; randomized control studies; treatment